Reliability and validity of the Chinese version of the retrospective family unpredictability scale - Qi, Wei; Xing, Chumeng; Ding, Luojin; Wang, Jingli; Guo, Dong; Xu, Yiye (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to revise the Chinese version of the Retrospective Family Unpredictability Scale (Retro-FUS-C) and evaluate its psychometric properties.MethodsTwo independent samples were collected through convenience sampling. Sample 1 (N = 277) was used for item analysis, parallel analysis, and exploratory factor analysis. Sample 2 (N = 612) was used to conduct confirmatory factor analysis, assess internal consistency, and examine criterion-related validity.ResultsThe revised Retro-FUS-C retained 18 items and identified a three-factor structure: parental discipline, maternal nurturance, and paternal nurturance. Confirmatory factor analysis supported the three-factor model with good model fit, and measurement invariance across gender was supported. Internal consistency was satisfactory (Cronbach's α = 0.76-−0.90; McDonald's ω = 0.85−0.95). Significant correlations with external measures supported criterion-related validity.ConclusionThe Retro-FUS-C provides a reliable and culturally appropriate tool for assessing retrospective family unpredictability among Chinese young adults, with potential utility in identifying individuals at risk for later psychological difficulties and informing prevention and intervention efforts.